Serum Granulysin in Differentiation of Stevens-Johnson Syndrome/toxic Epidermal Necrolysis and Erythema Multiforme - Huyen, Tran Thi; Hoa, Pham Dinh; Trang, Trinh Minh; Abe, Riichiro; Thuong, Nguyen Van; Lan, Pham Thi; Tirant, Michael (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute, life-threatening drug reactions, which lead to massive epidermal necrolysis. Granulysin plays an important role as a key mediator for keratinocyte apoptosis in these conditions. Erythema multiforme (EM) may have skin manifestation similar to SJS/TEN. AIMS: The aim of the study was to compare serum granulysin levels in patients with SJS/TEN and EM as well as to investigate a possible association between serum granulysin levels and the severity of SJS/TEN. METHODS: In total, 48 patients with SJS/TEN, 43 patients with EM, and 20 health controls (HCs) were enrolled. We measured serum granulysin levels using enzyme-linked immunosorbent assay. RESULTS: The average level of serum granulysin in the SJS/TEN patients was 23.0 ng/ml (range 1.2–144.6 ng/ml), significantly higher than that of EM group (20.1 ng/ml; range 8.5–121 ng/ml, p < 0.05) and HCs group (20.8 ng/ml; range 10.1–46.7 ng/ml, p < 0.05). Of 48 SJS/TEN patients, the 25 samples collected <6 days after onset showed higher level of serum granulysin (27.7 ng/ml; range 2.5–144.6 ng/ml) than those collected ≥6 days after onset (17.9 ng/ml; range 1.2–59 ng/ml; p > 0.05). No significant correlation was found between serum granulysin levels and the body surface area affected and the modified-SCORTEN. At the day of re-epithelialization, serum granulysin levels were not different compared with those at the day of hospitalization. CONCLUSIONS: Serum granulysin levels are significantly higher in SJS/TEN group than in EM group. After the onset, serum granulysin levels in patients with SJS/TEN are not a good biomarker to evaluate the severity of the diseases.